Literasi Keuangan Syariah dalam Era Digital: Membangun Kemandirian Ekonomi Masyarakat Desa Sendang: Sharia Financial Literacy in the Digital Age: Building Economic Independence of Sendang Village Community - Muhammad Adi Adrian; Kholid Albar; Adi Basuki Choirul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service article discusses the importance of Islamic financial literacy as a means to build economic independence in the Sendang Village, Bringin District, Semarang Regency, in the context of the digital era. In recent years, digitalization has changed the way people access financial information and products, offering new opportunities for local economic development. However, the level of Islamic financial literacy in the village remains low, leading to underutilization of available Islamic financial products. Through a needs analysis, this community service article identifies knowledge gaps among the community and evaluates the impact of Islamic financial literacy training on family economic management. The results of the community service show that improving the community's understanding of Islamic financial principles and the use of information technology can improve their economic independence. This article emphasizes the need for collaboration between various stakeholders, including Islamic financial institutions and the government, to create an ecosystem that supports financial literacy. Thus, Islamic financial literacy is not only a tool for increasing knowledge but also an important pillar for achieving sustainable economic prosperity. This research is expected to significantly contribute to the development of relevant and adaptive financial literacy programs for rural communities in the digital era.